Application of Aquaponic System as an Alternative for Medical Liquid Waste Containing Blood at the Dentist's Practice - Syifa Qurratu’ain; Purwanto; Dwi Kartika Apriyono; Tecky Indriana; Elyda Akhya Afida Misrohmasari (PT FORMOSA CENDEKIA GLOBAL, 2023)
The waste generated by the dentist clinic is in the form of non-medical waste and medical waste. Medical liquid waste containing blood can develop disease if not processing properly before entering the environment. Aquaponic system is a combination of hydroponics and aquatics, also the resirculation process using plants and animals as: convolvulus land (Ipoema Reptans) and catfishes (Clarias spp.) that able to survive the extremes. Aquaponic system has potential to be an alternative to treating medical liquid waste containing blood according to medical liquid waste standard in Regulation of the Minister of Environment of the Republic of Indonesia Number 5 of 2014. The study aims to observe the value changes of the liquid waste parameter as: BOD, COD, TSS, pH; and compare them to medical liquid waste standard. The research is a pre-experimental on shot case study that done in four days and put the treatment on the first day then the sample were taken every 24 hours. The measurement result of the liquid waste parameter has an efficiency as: BOD 57, 1%, COD 40 %, TSS 53 %, and pH 4, 7 %. All the parameter not exceeding the medical liquid waste standard in Regulation of the Minister of Environment of the Republic of Indonesia Number 5 of 2014. The conclusion is the application of an aquaponic system can be used as an alternative to medical liquid waste containing blood treatment